High Resolution Dynamical Analysis of Volatile Organic Compounds (VOC) Measurements During the BIO‐MAÏDO Field Campaign (Réunion Island, Indian Ocean). Issue 4 (8th February 2022) - Rocco, M.; Baray, J.‐L.; Colomb, A.; Borbon, A.; Dominutti, P.; Tulet, P.; Amelynck, C.; Schoon, N.; Verreyken, B.; Duflot, V.; Gros, V.; Sarda‐Estève, R.; et al.
Abstract: This study presents a high‐resolution dynamical analysis of Volatile Organic Compound (VOC) concentrations measured from March 11 to April 4 2019 at Réunion Island during the BIO‐MAÏDO (Bio‐physicochemistry of tropical clouds at Maïdo: processes and impacts on secondary organic aerosols formation) campaign. We detail the dynamical and chemical processes that govern atmospheric VOC concentrations at two targeted sites of the western slope of Réunion Island: Petite France (PF), 950 m above sea level (a.s.l.) and Maïdo Observatory (MO), 2150 m a.s.l. A dynamical connection between PF and MO is found during four selected days: March 28 and 31, April 1 and 3. Trajectory calculations using the coupling of Meso‐Computing Advection‐interpolation of atmospheric parameters and Trajectory tool (CAT) (100 m horizontal resolution of Meso‐NH high‐resolution non‐hydrostatic model and the CAT trajectory model) Lagrangian transport model showed that air masses were dynamically linked between the two measurements sites for 19% of the time during the complete campaign. Trajectories from the Meso‐CAT model combined with the Corine Land Cover‐2018 register shows that backward‐trajectories are frequently located above biogenic area (mixed forest, 3%–46% of total number trajectory point) and cultures area (e.g., sugar cane plantation, 1%–17%). Regarding VOCs concentrations, air masses coming from downhill MO are associated with significant measured concentrations of isoprene, isoprene oxidation products and benzene. Averaged concentration daytime ratios of isoprene and isoprene oxidation products from PF to MO are 0.73 ± 1.01 and 0.26 ± 0.26 respectively illustrating a loss of these VOCs due to deposition, oxidation, or possibility dilution on clouds. Key Points: Meso‐Computing Atmospheric Trajectory model show dynamical connections between two sites of the western slope of Réunion Island Coupling of air masses with the Corine Land Cover—2018 register show that the origin of backward trajectories are biogenic area (3%–46%) and cultures areas (1%–17%)